Influence of autochthonous lactic acid bacteria on the proteolysis, microstructure and sensory properties of low fat UF cheeses during ripening - Dragana Pesic Mikulec; Goran Trpkovic; Zorana Miloradovic; Zorica Radulovic; Jelena Miocinovic; Vladimir Pavlovic; Predrag Pudja (Mljekarstvo)
The influence of commercial bacteria Lactococcus lactis ssp. lactis and Lactococcus lactis ssp. cremoris (cheese A) and combinations of autochthonous lactic acid bacteria (LAB) strains Lactobacillus paracasei ssp. paracasei 08, Lactococcus lactis ssp. cremoris 656, Lactococcus lactis ssp. lactis 653 (cheese B and C) on composition, proteolysis, microstructure and sensory properties of low fat cheeses during ripening was investigated. Low fat cast ultra-filtered (UF) cheeses were produced according to the defined production procedure by mixing UF milk protein powder, skim milk and cream. Significant influence of different LAB strains on composition, primary proteolysis and microstructure was not found. Cheeses made with autochthonous LAB showed a higher rate of secondary proteolysis, as well as higher flavour scores, and were more acceptable than control cheese.